Permainan Media Edukatif Puzzle untuk Melatih Motorik Halus Siswa Kelas III SD Negeri 19 Desa Sukarami - Mawardah, Mutia; Pratiwi, Putri Ajeng (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Primary school education is the most critical educational process in the development of students. This is because primary school is the essential source of education for children to acquire knowledge after they have been educated by their parents at home, and it is a transition from kindergarten, where children have to adapt to a new environment, to the next level where they review not only games and songs but also primary school life. Six- to eight-year-olds begin to engage in learning to hone their cognitive skills. The method used is the puzzle educational media method; based on the results of the application of educational games at SD Negeri 19 Sukarami Village, it can be seen that children whose fine motoric development in writing was initially not smooth and slow are now writing quite well and are no longer left behind in writing material.